Cover Image, Volume 77, Issue 1‐2. Issue 1 (3rd February 2020) - Chou, Vivian T.; Johnson, Seth; Long, Jennifer; Vounatsos, Maxime; Van Vactor, David
Abstract : ON THE COVER: The front cover image is based on the Original Article dTACC restricts bouton addition and regulates microtubule organization at the Drosophila neuromuscular junction by David Van Vactor et al., https://doi.org/10.1002/cm.21578 .